Analysis Of The Influence Of Application Ease Of Use, Advertising Attractiveness And Consumer Trust On Purchasing Decisions On The Lazada Shopping Application In Padang City - Ramadhania Ramadhania; Ayu Ramadhani (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to determine and analyze the influence of ease of use of the application, attractiveness of advertising, and consumer trust partially and simultaneously on purchasing decisions on the Lazada shopping application in Padang City. The research method used is quantitative descriptive. The sampling technique used is purposive sampling using a sample of 100 respondents, data collection methods using interviews, questionnaires, and literature studies. Data analysis techniques used are multiple linear regression analysis, t-test, F-test, and coefficient of determination. Based on the multiple linear regression analysis obtained Y = 12.039 + 0.300 X1 + 0.561 X2 + 0.306 X3 + e. The results of the t-test showed that the attractiveness of advertising, ease of use of the application, and consumer trust have a positive and significant effect partially on purchasing decisions on Lazada in Padang City. The results of the F-test showed that ease of use of the application, attractiveness of advertising, and consumer trust have a significant effect on purchasing decisions on the Lazada shopping application in Padang City. The coefficient of determination is 75.2%, with the remaining 24.8% influenced by other variables outside this study, such as price, service quality, product reviews, and others.